New Ocean Subsurface Optical Properties From Space Lidars: CALIOP/CALIPSO and ATLAS/ICESat‐2. Issue 10 (4th October 2021) - Lu, Xiaomei; Hu, Yongxiang; Yang, Yuekui; Neumann, Thomas; Omar, Ali; Baize, Rosemary; Vaughan, Mark; Rodier, Sharon; Getzewich, Brian; Lucker, Patricia; Trepte, Charles; Hostetler, Chris; et al.
Abstract: Remote sensing from Earth‐observing satellites is now providing valuable information about ocean phytoplankton distributions. This paper presents the new ocean subsurface optical properties obtained from two space‐based lidars: the Cloud‐Aerosol Lidar with Orthogonal Polarization (CALIOP) aboard the Cloud‐Aerosol Lidar and Infrared Pathfinder Satellite Observations satellite and the Advanced Topographic Laser Altimeter System (ATLAS) aboard the Ice, Cloud, and land Elevation Satellite‐2 satellite. Obtaining reliable estimates of subsurface biomass necessitates removing instrument artifacts peculiar to each sensor, that is, polarization crosstalk artifacts in the CALIOP signals and after pulsing effects arising from the ATLAS photodetectors. We validate the optical properties derived from the corrected lidar backscatter signals using MODerate‐resolution Imaging Spectroradiometer ocean color measurements and autonomous biogeochemical Argo float profiles. Our results support the continued use of present and future spaceborne lidars to study the global plankton system and characterize its vertical structures in the upper ocean. Key Points: Global ocean subsurface properties are retrieved from Cloud‐Aerosol Lidar with Orthogonal Polarization (CALIOP) The CALIOP crosstalk artifact and Advanced Topographic Laser Altimeter System (ATLAS) after pulsing effects are removed High vertical resolution of ocean subsurface profiles can be obtained from ATLAS/Ice, Cloud, and land Elevation Satellite‐2